If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -44 = n + 8 Reorder the terms: -44 = 8 + n Solving -44 = 8 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -44 + -1n = 8 + n + -1n Combine like terms: n + -1n = 0 -44 + -1n = 8 + 0 -44 + -1n = 8 Add '44' to each side of the equation. -44 + 44 + -1n = 8 + 44 Combine like terms: -44 + 44 = 0 0 + -1n = 8 + 44 -1n = 8 + 44 Combine like terms: 8 + 44 = 52 -1n = 52 Divide each side by '-1'. n = -52 Simplifying n = -52
| (7x+1)(9x^2+4x+5)= | | n/3+4=10 | | M/3-14=10 | | 5y+5=4y-4 | | 0.22-0.02(x+3)=0.02(2-x) | | 6-wx=vx+2 | | 3=6+x/4 | | 9+(0.5x)= | | -5x+3=8 | | x(x-7)=458 | | 2/5y+3=6 | | 0.12-0.01(x+3)=-0.03(1-x) | | Y/3+25=48 | | 3/4p+7=16 | | 3/x=2/x-1 | | 31+w/3=31 | | k/8-9=6 | | 32+90x=78x+78 | | x/5-3=x/7-1 | | 4x+43=139 | | 22x+8x=160+22x | | 8(2x+1)-(x+3)=35 | | 39+3m=174 | | 4x+6x+50=20 | | 4x-26=2x+65 | | 42x^3-35x^2+14x=0 | | -7+x=8 | | 2(6v+7)=10(v+8) | | -1/2+3x=1 | | 35+3g=71 | | 8+x/7=16 | | 3x(7)-x=127 |